Sweetened beverage intake in association to energy and sugar consumption and cardiometabolic markers in children - Seferidi,P; Millett,C; Laverty,AA (Pediatric Obesity, 2017)
BackgroundArtificially sweetened beverages (ASBs) are promoted as healthy alternatives to sugarsweetened beverages (SSBs) in order to reduce sugar intake, but their effects on weight control and glycaemia have been debated. This study examines associations of SSBs and ASBs with energy and sugar intake and cardiometabolic measures.MethodsOne thousand six hundred eightyseven children aged 4–18 participated in the National Diet and Nutrition Survey Rolling Programme (2008/9–2011/12) in the UK. Linear regression was used to examine associations between SSBs and ASBs and energy and sugar, overall and from solid foods and beverages, and body mass index, waisttohip ratio and blood analytes. Fixed effects linear regression examined withinperson associations with energy and sugar.ResultsCompared with nonconsumption, SSB consumption was associated with higher sugar intake overall (6.1%; 4.2, 8.1) and ASB consumption with higher sugar intake from solid foods (1.7%; 0.5, 2.9) but not overall, mainly among boys. On SSB consumption days, energy and sugar intakes were higher (216 kcal; 163, 269 and 7.0%; 6.2, 7.8), and on ASB consumption days, sugar intake was lower (−1.0%; −1.8, −0.1) compared with those on nonconsumption days. SSB and ASB intakes were associated with higher levels of blood glucose (SSB: 0.30 mmol L−1; 0.11, 0.49 and ASB: 0.24 mmol L−1; 0.06, 0.43) and SSB intake with higher triglycerides (0.29 mmol L−1; 0.13, 0.46). No associations were found with other outcomes.ConclusionSugarsweetened beverage intake was associated with higher sugar intake and both SSBs and ASBs with a less healthy cardiometabolic profile. These findings add to evidence that health policy should discourage all sweetened beverage consumption.